Preeclampsia Neonatal Outcome in Pregnant Women with and without Gestational Diabetes Mellitus and Polycystic Ovary Syndrome - Akram Hemmatipur; Azam Jahangiri Mehr; Elham Touriaie; Masoumeh Salehi Kombu (Mashhad University of Medical Sciences, 2018)
Introduction: Gestational diabetes mellitus is the most common metabolic disorder. Polycystic ovary syndrome (PCO) is one of the most important causes of infertility during the fertility period, resulting in preeclampsia and many maternal and fetal complications. Methods: This case-control study was conducted on 152 pregnant women with preeclampsia admitted to the Maternity Ward of Shoushtar Al-Hadi Hospital in 2016-2017. The study population was assigned of case (n=76) and control (n=76) based on infliction with gestational diabetes mellitus and PCO. Data analysis was performed in SPSS (version 16) using Kolmogorov-Smirnov test, independent t-test, and Chi-square test. P-value less than 0.05 was considered statistically significant. Results: The mean ages of the mothers and pregnancy termination were 31±6 years and 34±5.02 months, respectively. There was a statistically significant difference between the two groups in terms of the history of PCO, infertility, gestational diabetes, and preeclampsia, as well as, body mass index (P<0.001). Among the neonatal complications, the two groups were significantly different regarding the decreased intrauterine growth (P=0.03). In this regard, the ratio of decreased intrauterine growth was 2.1 times higher in the case group, compared to that in the control group (OR: -1.2, CI: 1.76-2.46). Conclusion: Gestational diabetes mellitus and polycystic ovarian syndrome in the presence of preeclampsia are associated with a significant reduction in fetal intrauterine growth.